Effect of cadmium on the defense response of Pacific oyster Crassostrea gigas to Listonella anguillarum challenge - 丛明 吕家森 吴惠丰 赵建民 (Chinese journal of oceanology and limnology, 2013)
Heavy metal pollution can affect the immune capability of organisms. We evaluated the effect of cadmium （Cd） on the defense responses of the Pacific oyster Crassostrea gigas to Listonella anguillarum challenge. The activities of several important defensive enzymes, including superoxide dismutase （SOD）, glutathione peroxidase （GPx）, acid phosphatase （ACP）, Na＋, K＋-ATPase in gills and hepatopancreas, and phenoloxidase-like （POL） enzyme in hemolymph were assayed. In addition, the expression levels of several genes, including heat shock protein 90 （IrtSP9~））, metallothionein （MT）, and bactericidal/permeability increasing （BPI） protein were quantified by fluorescent quantitative PCR. The enzyme activities of SOD, ACP, POL, and GPx in hepatopancreas, and the expression of HSP90 were down-regulated, whereas GPx activity in the gill, Na＋, K＋-ATPase activities in both tissues, and MT expression was increased in Cd- exposed oysters post L. anguillarum challenge. However, BPI expression was not significantly altered by co-stress of L. anguillarum infection and cadmium exposure. Our results suggest that cadmium exposure alters the oysters＇ immune responses and energy metabolism following vibrio infection.